Congratulations to our new Deputy Rectors - Ch’ng, Looi Chin (UiTM Sarawak, 2018)
Their appointment marks a significant milestone for the university as we continue striving for excellence. With their experience, dedication, and passion for education, we are confident they will bring fresh perspectives, strong leadership, and innovative strategies that will inspire both staff and students.